2010
DOI: 10.1103/physrevc.82.054312
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic and antiferromagnetic spin-ordering stabilities of asymmetric nuclear matter: Lowest-order constrained variational method

Abstract: In this paper we study the possibility of spontaneous ferromagnetic and antiferromagnetic phase transitions of asymmetrical nuclear matter using the lowest-order constrained variational technique with AV 18 potential and employing a microscopic point of view. Our results show that the spontaneous transition to ferromagnetic and antiferromagnetic phases cannot occur for asymmetric nuclear matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…In fact, many effective nuclear interactions of Skyrme [22,23] or Gogny [24] type predict this transition at densities accesible in neutron stars. However, in accordance with the reduction of the spin susceptibility comented above, microscopic calculations based on realistic interactions do not predict such transition at least in the wide range of densities which have been explored [1][2][3][4][5][6][7]. The study of spin-polarization has also been recently considered for nuclear matter and finite nuclei using finite range effective interactions [25].…”
Section: Introductionmentioning
confidence: 95%
“…In fact, many effective nuclear interactions of Skyrme [22,23] or Gogny [24] type predict this transition at densities accesible in neutron stars. However, in accordance with the reduction of the spin susceptibility comented above, microscopic calculations based on realistic interactions do not predict such transition at least in the wide range of densities which have been explored [1][2][3][4][5][6][7]. The study of spin-polarization has also been recently considered for nuclear matter and finite nuclei using finite range effective interactions [25].…”
Section: Introductionmentioning
confidence: 95%
“…It should be mentioned that the cases δ p = δ n = 0, δ p = δ n and δ p = −δ n are called the unpolarized, ferromagnetic and antiferromagnetic states, respectively [23,24]. Ferromagnetic and antiferromagnetic states may also called polarized states.…”
Section: Resultsmentioning
confidence: 99%
“…By solving these differential equations, we can obtain correlation functions to compute the two-body energy term. For more details see Refs [21,23].…”
Section: Finite Temperature Calculations For Spin Polarized Nu-clmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the behavior of spin polarization of neutron matter in the high density region in a strong magnetic field crucially depends on whether neutron matter develops a spontaneous spin polarization (in the absence of a magnetic field) at several times nuclear matter saturation density, or the appearance of a spontaneous polarization is not allowed at the relevant densities (or delayed to much higher densities). The first case is usual for the Skyrme forces [13][14][15][16][17][18][19][20][21][22][23], while the second one is characteristic for the realistic nucleon-nucleon (NN) interaction [24][25][26][27][28][29][30][31][32]. In the former case, a ferromagnetic transition to a totally spin polarized state occurs while in the latter case a ferromagnetic transition is excluded at all relevant densities and the spin polarization remains quite low even in the high density region.…”
Section: Introductionmentioning
confidence: 99%